On ancient medicine and food: an interview with John Wilkins - Wilkins, John; Carvalho, Margarida Maria de; Junqueira, Nathalia Monseff (Romanitas - Revista de Estudos Grecolatinos, 2025)
Interview with John Wilkins, Emeritus Professor of Classical Studies at the University of Exeter, United Kingdom, a specialist in the History of Food and Medicine in the Greco-Roman World, and a member of the scientific committee of the journal Food and History, published by the European Institute of Food History and Cultures.
Keywords: John Wilkins; Food; Medicine; Antiquity